\[\boxed{\text{261\ (261).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ f(x) = \frac{1}{3}x + 12\]
\[\frac{1}{3}x + 12 = 0\]
\[\frac{1}{3}x = - 12\]
\[x = - 36.\ \]
\[Ответ:x = - 36\]
\[2)\ f(x) = 6x^{2} + 5x + 1\]
\[6x^{2} + 5x + 1 = 0\]
\[D = 25 - 24 = 1\]
\[x = \frac{- 5 \pm 1}{12}\]
\[x = - \frac{1}{2};\ \ \ x = - \frac{1}{3}.\]
\[Ответ:x = - \frac{1}{3};\ \ x = - 0,5.\]
\[3)\ f(x) = \sqrt{x^{2} - 4}\]
\[x^{2} - 4 = 0\]
\[x^{2} = 4\]
\[x = \pm 2.\]
\[Ответ:x = \pm 2.\]
\[4)\ f(x) = - 5\]
\[Ответ:\ нулей\ функции\ нет.\]
\[5)\ f(x) = \frac{3 - 0,2x}{x + 1};\ \ x \neq - 1\]
\[3 - 0,2x = 0\]
\[0,2x = 3\]
\[x = 15.\]
\[Ответ:x = 15.\]
\[6)\ f(x) = x^{2} - x\]
\[x^{2} - x = 0\]
\[x \cdot (x - 1) = 0\]
\[x = 0;\ \ x = 1.\]
\(Ответ:x = 0;\ \ x = 1.\)
\[\boxed{\mathbf{261.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ (2 - y)(3 + y) \leq (4 + y)(6 - y)\]
\[6 - 3y + 2y - y^{2} \leq 24 + 6y - 4y + y^{2}\]
\[- y - 2y \leq 24 - 6\]
\[- 3y \leq 18\]
\[y \geq - 6.\]
\[2)\ \frac{y - 1}{2} - \frac{2y + 1}{8} - y < 2\ \ \ | \cdot 8\]
\[4(y - 1) - 2y - 1 - 8y < 16\]
\[4y - 4 - 10y - 1 < 16\]
\[- 6y < 21\]
\[y > - \frac{21}{6}\]
\[y > - \frac{7}{2}\]
\[y > - 3,5.\]